EFEKTIFITAS METODE TEPID SPONGE DAN KOMPRES DINGIN DALAM MENURUNKAN SUHU TUBUH ANAK DEMAM - Aguspairi Aguspairi (Jurnal Ilmiah Universitas Batanghari Jambi, 2011)
Compress is one of the methods of physics in lowering body temperature. Compress is one way of removing heat from the body by direct contact between one object with another object, or better known kenduksi process. How to compress to lower fever, such as by providing a warm compress, compress cold water, using ice cubes, alcohol, cold blanket (blanket hypothermia), the use of air conditioner and ceiling fan as well as methods of tepid sponge. This study was quasi experimental with two group pretest-post test only design the form of Pre and Post Design. The population in this study were all under five with fever and number of a sample of 20 respondents. The mean decrease in body temperature of infants after a given method of tepid sponges of 1.27 ° C, while the decrease in body temperature of infants after being given a cold compress by 0.63 oC. Tepid sponges compress method is more effective in lowering body temperature under five with fever. Statistical test results obtained value    p-value = 0.000, smaller than 0.05 in other words, there were significant differences between the toddler's body temperature drop of tepid sponges compress method and cold compresses.keyword: sick, tepid sponge